Outcome of Ewing sarcoma in a multidisciplinary setting in Lebanon. Issue 8 (7th January 2014) - Abou Ali, Bilal; Nader, Ralph; Tamim, Hani; Eid, Toufic; Boulos, Fouad; Khoury, Nabil; Akel, Samir; Haidar, Rachid; Saghieh, Said; Abboud, Miguel; Muwakkit, Samar; El‐Solh, Hassan; et al.
<x xml:space="preserve">Abstract</x> Treatment of Ewing sarcoma (ES) necessitates coordinated multi‐disciplinary care. We analyzed outcome for 39 patients treated at a single institution in Lebanon, a developing country with available multidisciplinary treatment modalities, where financial barriers to care are overcome by a fundraising system. Median follow‐up was 58 months. Five‐year overall and event‐free survival were 76% and 58%, respectively, for localized disease, and 40% and 38%, respectively, for metastatic disease. We conclude that, in a country with emerging economy, by following international protocols and ensuring availability of needed resources, outcome of patients with ES is similar to that in developed countries. Pediatr Blood Cancer 2014; 61:1472–1475. © 2014 Wiley Periodicals, Inc.